Phenolic profile, antioxidant, anti-inflammatory and anticancer activities of Telephium imperati L. - Benarba, Bachir; Belhouala, Khadidja; Korkmaz, Cansu; Küçükaydın, Meltem Taş; Küçükaydın, Selçuk; Duru, Mehmet Emin (Journal of Phytology, 2024)
Telephium imperati L. is one of the most valuable spices used by Algerians for food and different medicinal purposes. Here, we report the main phenolic compounds of T. imperati that grows in arid regions and its antioxidant, anti-inflammatory, and anticancer activities. The phenolic profiles of methanolic and aqueous extracts of T. imperati roots was obtained using HPLC-DAD, whereas antioxidant activity was evaluated using 2.2-diphenyl-1-picrylhydrazyl (DPPH), potassium ferricyanide, and Hydrogen peroxide (H2O2) assays. Moreover, the anti-inflammatory activity was investigated by measuring the level of protection of the human red blood cell (HRBC) membrane against hypotonicity-induced lysis. The anticancer activity was evaluated using the MTT assay against three human cancer cell lines (HT-29, PC-3, A-549) and one non-tumorigenic (CCD18-Co) cells. Our results showed that the methanolic extract was rich in phenols (493.17±0.0 mg GAE/g), flavonoids (271.56±0.1 mg QE/g), and tannins (106.50±2.3 mg CE/g). The HPLC-DAD analysis revealed that caffeic acid (78.61 mg/g), ferulic acid (49.12 mg/g), rosmarinic acid (42.80 mg/g), coumarin (39.87 mg/g), rutin (37.68 mg/g), myricetin (25.62 mg/g), syringic acid (18.90 mg/g), and quercetin (18.65 mg/g) were mainly present in T. imperati extracts. Although the DPPH assay showed slight antioxidant activity for both extracts, the methanolic extract exhibited significant potent anti-inflammatory action in all in vitro tests, protecting HRBC damage and BSA denaturation at rates of 80.18 and 97.62%, respectively. Likewise, the methanolic extract exhibited an important anticancer activity against the HT-29 and A-549 cell lines, with IC50 values ranging from 1.85 to 2.00 log10 μg/mL. Interestingly, no toxic effects on CCD18-Co were observed. Therefore, the present study revealed that T. imperati root extracts are rich in phenolic compounds and could be a promising source of anti-inflammatory and anticancer molecules.